Analysis of Hydrogen Bonds in Crystals - Sławomir J. Grabowski (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
There is no doubt that the hydrogen bond is one of the most-often analyzed interactions, and there is also no doubt that experimental studies, especially those based on the determination of crystal structures are very important since they deliver valuable information on the nature of this interaction, on different types of the hydrogen bonds, and also on reactions where a hydrogen bond may be treated as the preliminary step. Since the role of the analysis of crystal structures for investigations concerning hydrogen-bonded systems is valuable, the Editorial Board of Crystals, thus, decided to devote a Special Issue of the journal to the analysis of hydrogen bonds in crystals.